Analysis of social welfare program and married women labor participation in West Sumatra - Isra Yeni; Urmatul Uska Akbar; Yollit Permata Sari; Idris Idris; Melti Roza Adry; Dewi Zaini Putri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
Social welfare program from the government has a role in reducing poverty rates and improving the welfare of poor households. Through social assistance, it can increase household income and indirectly alleviate the need for women to work. This study aims to analyze the effect of government social assistance on the probability of married women participating in the labor market. This study uses secondary data from the National Socio-Economic Survey (SUSENAS) in 2019 in West Sumatra. Using the logit model, the results of this study show that married women who are receiving social assistance have a greater opportunity to participate in the labor market.